Bikini textile contact dermatitis: A Sherlockian approach revealing 2, 4‐dichlorophenol as a potential textile contact allergen. (4th August 2021) - Pesqué, David; March‐Rodriguez, Álvaro; Dahlin, Jakob; Isaksson, Marléne; Pujol, Ramon M.; Giménez‐Arnau, Elena; Giménez‐Arnau, Ana M.
Abstract: Background: Different textile constituents may act as allergens and/or irritants and provoke textile contact dermatitis (TCD). Objectives: To report a case of TCD caused by ethylene glycol monododecyl ether and 2, 4‐dichlorophenol, present in a bikini. Methods: A woman presented with an eczematous, pruritic rash in the area of the bikini straps and back. Patch testing was performed with the European baseline, textile, sunscreen, and photo‐patch series, the bikini "as is", and ethanol and acetone extracts of the bikini. Thin‐layer chromatography (TLC) of the extracts and gas chromatography–mass spectrometry (GC–MS) analysis were used to elucidate the culprit agents. Results: Positive reactions were found to the bikini "as is" and to the ethanol and acetone extracts. Patch testing with TLC strips showed a strong reaction to spots‐fractions 3 and 4. GC–MS was performed to identify substances in each fraction and those suspected to be skin sensitisers were patch tested. On day (D) 4 positive reactions to ethylene glycol monododecyl ether (irritant reaction) and 2, 4‐dichlorophenol (++) were observed. Conclusion: A myriad of chemical compounds can be found in clothing. Ethylene glycol monododecyl ether and 2, 4‐dichlorophenol were identified as the potential culprits of this bikini TCD. Highlights: We have combined chemical analyses (thin‐layer chromatography and gas chromatography–mass spectrometry) to study a case of textile contact dermatitis. As such, the presence of a myriad of chemical compounds was found in a bikini, suggesting that clothing in general may become impregnated or contaminated by a wide range of external substances that may be harmful to the skin. Textile contact dermatitis could in this case be attributed to ethylene glycol monododecyl ether (CAS No. 4536‐30‐5) and 2, 4‐dichlorophenol (CAS No. 120‐83‐2), the latter not yet previously described as a textile contact allergen.